The Bellwomen - Stockford, Marjorie A., 1957- (Book collections on Project MUSE., 2004)
"In the early 1970s, David Copus, a young lawyer, teamed up with his government colleagues to confront the mature and staid executives of AT & T over the company's treatment of its female and minority employees. Their disagreement resulted in a $38 million settlement that benefited 15,000 employees, more than 13,000 of them women, and changed our perceptions of women's and men's roles in the workplace forever." "Copus, who worked for the Equal Employment Opportunity Commission (EEOC), was charged with representing American citizens who suffered from employment discrimination. Time and again he saw young, black women in the South being turned down for available jobs in local phone companies - usually as telephone operators - often for no valid reason. He and the EEOC decided to challenge AT & T's company-wide sex discrimination practices. Eventually, AT & T's corporate colleagues, witnessing AT & T's capitulation, began to hire and promote women into better jobs themselves. At the same time, the EEOC started to aggressively push corporate America to give women more opportunities." "The Bellwomen recounts the history of this case in a novelistic style, illuminating the motivations, strengths, and weaknesses of all the players, from AT & T corporate leaders, to the lawyers of the EEOC, to the female activists fighting for what they believed. Stockford also profiles three beneficiaries of the case, presenting their ambitions and achievements."--Jacket.